PENGARUH CAMPURAN LIMBAH PLASTIK LDPE DAN POLYPROPYLENE SEBAGAI SUBSTITUSI CAMPURAN ASPAL TERHADAP CAMPURAN AC-WC - Muhammad Vallery Al Tansha; Tiana Fatwa Maharani; Dafrimon; Amiruddin (Politeknik Negeri Sriwijaya, 2024)
In Indonesia, the most frequently used pavement for road construction is flexible pavement with the main material using asphalt. Caused of that, needed to develop asphalt technology to improve asphalt quality. One of alternative that can be used is modifying asphalt by adding other polymer materials, plastic. This study aims to determine the effect of a mixture of Low Density Polyethylene (LDPE) and Polypropylene plastic to Asphalt Concrete Wearing Course (AC-WC) mixture. Furthermore, first stage of this research is making specimens to find the Optimum Asphalt Value (KAO), then making Marshall specimens by substituting a mixture of LDPE and Polypropylene plastic with a variation of 3%; 4%; 5%; 6%; and 7% for the optimum asphalt content. Based on the results of the analysis of the Marshall characteristics data on the plastic mixture test object, the most optimum percentage of plastic value obtained is 1529,450 kg(stability value), for the flow value is 3,018 mm, VIM value is 4,950%, VFA value is 67.089%, VMA value is 15.044% and Marshall Quotient value is 506.860 %.